GPU-based visualization of knee-form contact area for safety inspections. Issue 3 (16th April 2017) - Inui, Masatomo; Nakano, Shunsuke; Umezu, Nobuyuki; Asano, Tetsuya
Abstract : The United Nations defines a safety regulation based on the possible collision between the driver's knee and an automobile's instrument panel. The "knee-form" apparatus used to evaluate compliance with this regulation can be modeled as a Minkowski sum shape of a vertical equilateral triangle and a horizontal cylinder with a radius of 60 mm and a thickness of 120 mm. The knee form contacting condition is geometrically equivalent to that of an equilateral triangle contacting a Minkowski sum shape of the instrument panel and a horizontal cylinder. Based on this concept, we propose a novel algorithm for extracting the knee-form contacting area on the instrument panel. With the parallel computation capability of a Graphics Processing Unit, our system can detect and output the knee-form contacting area in a practical time period. GRAPHICAL ABSTRACT: